Peran Audit Internal Atas Kualitas Pemeriksaan Laporan Keuangan Yang Dilakukan Oleh Audit Eksternal Pada Sebuah Perusahaan - Arista Puji Utami; Nunky Vinalia; Ilyas Febriyan; Brian Gamara Putra; Herlina Manurung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to research the role of internal auditor to the quality of financial reporting. Financial reporting is an important part as consideration to make a decision. Therefore, the quality of financial reporting needs to be observed because it affects stakeholders’ decision. Nowadays, the role of internal audit is highlighted as one of the important roles to improve the quality of financial reporting.The samples used are Internal Audit working in a company. The dependent variable in this study is the quality of financial statements, while the independent variable is Internal Audit. The results of this research shows that the internal auditor has a positive and significant role on the quality of financial reporting. The more the internal auditor involves in monitoring the reliability of financial reporting, the better quality of financial reporting will be.